2019
DOI: 10.1016/j.cell.2018.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation Permanently Reshapes Tissue-Resident Immunity in Celiac Disease

Abstract: SUMMARY Tissue-resident lymphocytes play a key role in immune surveillance, but it remains unclear how these inherently stable cell populations respond to chronic inflammation. In the setting of celiac disease (CeD), where exposure to dietary antigen can be controlled, gluten-induced inflammation triggered a profound depletion of naturally occurring Vγ4+/Vδ1+ intraepithelial lymphocytes (IELs) with innate cytolytic properties and specificity for the butyrophilin-like (BTNL) molecules BTNL3/BTNL8. Creation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
148
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(173 citation statements)
references
References 56 publications
13
148
4
Order By: Relevance
“…The majority of intestinal TCRγδ + T cells expressed the Vδ1 chain, in agreement with previous studies where it was demonstrated that Vδ1 + T cells constituted the highest fraction of all intestinal TCRγδ + cells in CD patients with active disease.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of intestinal TCRγδ + T cells expressed the Vδ1 chain, in agreement with previous studies where it was demonstrated that Vδ1 + T cells constituted the highest fraction of all intestinal TCRγδ + cells in CD patients with active disease.…”
Section: Discussionsupporting
confidence: 92%
“…As the byproduct 420 of incomplete beta oxidation, the increased isobutyry-l-carnitine is related to abnormalities in 421 fatty acid metabolism 65 and activates proinflammatory signaling 66 Currently, the only way to treat CD is strict adherence to a gluten-free (GF) diet, but 20% 428 of patients do not respond to GF diet and continue to have persistent or recurrent symptoms 67 . 429 CD permanently reshapes intestinal immunity and alterations in TCRγδ+ intraepithelial 430 lymphocytes in particular may underlie non-responsiveness to the GF diet 68 . Our findings 431 suggest that the inflammatory nature of the CD progressors' gut microbiota is a key component 432 of intestinal inflammation in CD.…”
Section: Discussion 328mentioning
confidence: 99%
“…Similar innate-like phenotypes can be ascribed to human gut-resident Vγ4 + intestinal epithelial γδ T cells (IELs), that are CD69 + and express the natural cytotoxicity receptors Nkp46 and/or Nkp44 [38,110]. Human Vγ4 + IELs are shaped and selected by the BTNL-like molecules, BTNL3 and BTNL8, that are exclusively expressed in the human gut epithelial [14].…”
Section: Tissue-resident γδ Tcr Repertoiresmentioning
confidence: 91%